2003
DOI: 10.1116/1.1542616
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of gel formation and surface and line-edge roughness in negative tone chemically amplified resists

Abstract: Simulation of amine concentration dependence on line edge roughness after development in electron beam lithography J. Appl. Phys.Surface and line-edge roughness in solution and plasma developed negative tone resists: Experiment and simulation J.A molecular-based representation of a negative tone chemically amplified resist was developed and studied using stochastic simulations. The gel formation mechanism resulting from the reactiondiffusion phenomena in the polymer matrix during the postexposure bake step, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A stochastic dissolution simulator built to model reactiondiffusion phenomena in negative tone chemically amplified resists, [10][11][12] was modified accordingly, in order to simulate positive tone resist deprotection chemistry and dissolution. 9,13) Dissolution modeling was based on the notion of critical ionization fraction 14) and was combined with the code for modeling polymer chains, and postexposure bake.…”
Section: Model Descriptionmentioning
confidence: 99%
“…A stochastic dissolution simulator built to model reactiondiffusion phenomena in negative tone chemically amplified resists, [10][11][12] was modified accordingly, in order to simulate positive tone resist deprotection chemistry and dissolution. 9,13) Dissolution modeling was based on the notion of critical ionization fraction 14) and was combined with the code for modeling polymer chains, and postexposure bake.…”
Section: Model Descriptionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38] Probabilisticlike models also find applications, 39 as well as variants of the percolation dissolution, such as the aggregate extraction dissolution model. The rate of dissolution of the resist film is controlled by the diffusion of base through a so-called "penetration zone."…”
Section: Introductionmentioning
confidence: 99%
“…However, the same effect is accompanied by resist line profile distortion, especially in the resist/line case [32,38]. Simulations [5] have also predicted the same, and this has been justified in terms of the acid diffusion, which softens the difference in exposure between neighboring regions of the resist line to the intermediate region between exposed and un-exposed film. It has been reported that the use of low molecular weight and low dispersivity polymers as resist films decreases roughness and acid diffusion range [39].…”
Section: Resist Film Surface and Line-edge Roughnessmentioning
confidence: 77%
“…In this article the simulation of positive tone resists, is done along the same lines with previous work [5]. All polymer chains have the same polymerization length, which is given as input in the simulations.…”
Section: Simulation Of Dissolution and Roughness Formationmentioning
confidence: 99%
See 1 more Smart Citation